Pengaruh Pembelajaran Sains Menggunakan LKPD Berbasis Problem Based Learning (PBL) Terhadap Kemampuan Berpikir Kritis Bagi Siswa Sekolah Dasar - Prasthiyo A.D.W, Anthon; Widi Winarni, Endang; Muktadir, Abdul (Jurnal Kajian Pendidikan Dasar, 2025)
The purpose of this research is to analyze the influence of science learning using problem-based LKPD on the dimensions of focus, reason, and inference thinking abilities, as well as to analyze the relationship between focus, reason, and inference thinking abilities in science learning using problem-based LKPD. The type of research used is quasi-experimental research using a pretest-posttest control group design. The instruments used are a questionnaire and an expert validation sheet. Based on the two-tailed Asymp sig. value, it is 0.000 < 0.05. It can be concluded that the use of problem-based LKPD in science learning significantly affects the dimensions of focus, reasoning, and inference thinking skills. Furthermore, there is a significant relationship in the dimension of focus thinking ability with reasoning using problem-based LKPD in science learning, while for inference thinking ability, there is no significant relationship with focus thinking and reasoning ability.